ROS Function in Redox Signaling and Oxidative Stress - Schieber, Michael (2014)
Oxidative stress refers to elevated intracellular levels of reactive oxygen species (ROS) that cause damage to lipids, proteins and DNA. Oxidative stress has been linked to a myriad of pathologies. However, elevated ROS are also signaling molecules i.e. redox biology that maintain physiological functions. In this review we discuss the two faces of ROS, redox signaling and oxidative stress, and their contribution to both physiological and pathological conditions. Redox biology refers to low levels of ROS that activate signaling pathways to initiate biological processes while oxidative stress denotes high levels of ROS that incur damage to DNA, protein or lipids. Thus, the response to ROS displays hormesis. The In this review, we argue that redox biology, rather than oxidative stress, underlies physiological and pathological conditions.